A Step-By-Step Guide to Tier 2 Behavioral Progress Monitoring. (April 2018) - Bruhn, Allison L.; McDaniel, Sara C.; Rila, Ashley; Estrapala, Sara
Students who are at risk for or show low-intensity behavioral problems may need targeted, Tier 2 interventions. Often, Tier 2 problem-solving teams are charged with monitoring student responsiveness to intervention. This process may be difficult for those who are not trained in data collection and analysis procedures. To aid practitioners in these worthwhile tasks, we offer a step-by-step guide to collecting and evaluating Tier 2 behavioral progress monitoring data. This systematic approach includes (a) selecting an appropriate method of measurement, (b) planning for data collection and evaluation, (c) collecting and analyzing data, (d) considering treatment fidelity, and (e) adjusting intervention based on student responsiveness. Each step is described in detail with specific examples and additional resources are provided.